Retorika Aristoteles Pendeta Steve Marcel dalam Konten Youtube Deddy Corbuzier - Tri Rizky Ramadhan; Zuhry, Audi Alya; Khumairoh, Viny; Hindun, Hindun (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2025)
The purpose of this study is to find and explain the ethos, pathos, and logos aspects of Pastor Steve Marcel contained in the Deddy Corbuzier Youtube channel in the Login program. The research uses qualitative methods. The data collection technique is carried out by watching, listening. The data obtained was then analyzed using Aristotle's theory. The results found in this study include ethos which include character views, intelligence views, and goodwill views, pathos include language styles based on tone structure, language styles based on sentence structure, the use of appropriate facial expressions, and the use of emphasis techniques, logos include enthymeme (entimem) and examples